ChemInform Abstract: Annuloselectivity in Reactions of Diacyl Dichlorides and Imines: Combined Experimental and Theoretical Studies. Issue 46 (November 2015) - Li, Xinyao; Jin, Xin; Xu, Jiaxi
Abstract The selectivity between [2+2] and cascade annulation of diacyl chlorides and imines in the presence of Et3N leading to bis‐β‐lactams and/or 2, 3‐dihydro‐1, 3‐oxazin‐4‐ones is studied.